Implementing psychosocial interventions within low and middle-income countries to improve community-based care for people with psychosis—A situation analysis - Bird, Victoria Jane; Davis, Syjo; Jawed, Abeer; Qureshi, Onaiza; Ramachandran, Padmavati; Shahab, Areeba; Venkatraman, Lakshmi (Frontiers in Psychiatry, 2022)
Background: Globally, a treatment gap exists for individuals with severe mental illness, with 75% of people with psychosis failing to receive appropriate care. This is most pronounced in low and middle-income countries, where there are neither the financial nor human resources to provide high-quality community-based care. Low-cost, evidence-based interventions are urgently needed to address this treatment gap. Aim: To conduct a situation analysis to i) describe the provision of psychosocial interventions within the context of existing care in two LMICs - India and Pakistan, and ii) understand the barriers and facilitators of delivering a new psychosocial intervention. Method: A situation analysis was conducted including a quantitative survey and individual interviews with clinicians, patients and caregivers. Quantitative survey data was collected from staff members at 11 sites (private and government run hospitals) to assess organisational readiness to implement a new psychosocial intervention. To obtain in-depth information, 24 stakeholders including clinicians and service managers were interviewed about the typical care they provide and/or receive, and their experience of either accessing or delivering psychosocial interventions. This was triangulated by six interviews with carer and patient representatives. Results and discussion: The results highlight the positive views toward psychosocial interventions within routine care and the enthusiasm for multidisciplinary working. However, barriers to implementation such as clinician time, individual attitudes towards psychosocial interventions and organisational concerns including the lack of space within the facility were highlighted. Such barriers need to be taken into consideration when designing how best to implement and sustain new psychosocial interventions for the community treatment of psychosis within LMICs.